THE EFFECT OF PLACEMENT AND WORK CLIMATE ON EMPLOYEE WORK PRODUCTIVITY IN NATIONAL EDUCATION AUTHORITIES EAST OKU DISTRICT - Helisia Margahana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
His study aims to analyze partially and jointly the effect of placement, work climate on employee productivity and to analyze the most dominant variables in influencing the work productivity of employees at the East OKU District National Education Office, the results of regression analysis and the correlation between job placement and work climate. employees show a regression model. The results showed that joint placement (X1) and work climate (X2) had a significant effect on work productivity (Y), but had a more dominant effect on the work climate, namely Y = 5.309 + 0.683X1 + 0.292X2 + e with a coefficient of 0.911 at 95% confidence level, found that placement and climate can simultaneously predict employee productivity. For the East OKU Regency National Education Office, in building employee work organizations, organizations that play an important role, employees who need a conducive and comfortable climate. Organizational climate can be measured by the sense of responsibility that everyone has, as well as how work standards and job expectations are generated. Employees need rewards for recognition of their work. Efforts to increase employee productivity, leaders must place employees according to their educational background with their field of work, increase employee productivity, listen to employee suggestions and opinions, provide motivation, are reliable and involve the role of employees so that employees can show better performance.